Reconciling the understanding of 'hydrophobicity' with physics-based models of proteins. (2nd February 2016) - Harris, Robert C; Pettitt, B Montgomery
Abstract: The idea that a 'hydrophobic energy' drives protein folding, aggregation, and binding by favoring the sequestration of bulky residues from water into the protein interior is widespread. The solvation free energies ( ) of small nonpolar solutes increase with surface area ( A ), and the free energies of creating macroscopic cavities in water increase linearly with A . These observations seem to imply that there is a hydrophobic component ( ) of that increases linearly with A, and this assumption is widely used in implicit solvent models. However, some explicit-solvent molecular dynamics studies appear to contradict these ideas. For example, one definition ( ) of is that it is the free energy of turning on the Lennard–Jones (LJ) interactions between the solute and solvent. However, decreases with A for alanine and glycine peptides. Here we argue that these apparent contradictions can be reconciled by defining to be a near hard core insertion energy ( ), as in the partitioning proposed by Weeks, Chandler, and Andersen. However, recent results have shown that is not a simple function of geometric properties of the molecule, such as A and the molecular volume, and that the free energy of turning on the attractive part of the LJ potential cannot be computed from first-order perturbation theory for proteins. The theories that have been developed from these assumptions to predict are therefore inadequate for proteins.